Bovine herpesvirus 4-based vector delivering a hybrid rat/human HER-2 oncoantigen efficiently protects mice from autochthonous Her-2+ mammary cancer. (3rd March 2016) - Jacca, Sarah; Rolih, Valeria; Quaglino, Elena; Franceschi, Valentina; Tebaldi, Giulia; Bolli, Elisabetta; Rosamilia, Alfonso; Ottonello, Simone; Cavallo, Federica; Donofrio, Gaetano
ABSTRACT: The epidermal growth factor receptor 2 (HER-2) oncogene is a major target for the immunotherapy of breast cancer. Following up to the therapeutic success achieved with Her-2-targeting monoclonal antibodies, immune-prophylactic approaches directed against Her-2 have also been investigated taking into account, and trying to overcome, Her-2 self-tolerance. Perhaps due to safety (and efficacy) concerns, the least explored anti-Her-2 active immunization strategy so far has been the one relying on viral-vectored vaccine formulations. Taking advantage of the favorable properties of bovine herpesvirus 4 (BoHV-4) in terms of safety and ease of manipulation as well as its previously documented ability to transduce and confer immunogenicity to heterologous antigens, we tested the ability of different recombinant HER-2-BoHV-4 immunogens to 8break tolerance and elicit a protective, anti-mammary tumor antibody response in HER-2 transgenic BALB-neuT mice. All the tested constructs expressed the HER-2 transgenes at high levels and elicited significant cellular immune responses in BALB/c mice upon administration via either DNA vaccination or viral infection. In BALB-neuT mice, instead, only the viral construct expressing the membrane-bound chimeric form of Her-2 protein (BoHV-4-RHuT-gD) elicited a humoral immune response that was more intense and earlier-appearing than that induced by DNA vaccination. In keeping with this observation, two administrations of BoHV-4-RHuT-gD effectively protected BALB-neuT mice from tumor formation, with 50% of vaccinated animals tumor-free after 30 weeks from immunization compared to 100% of animals exhibiting at least one palpable tumor in the case of animals vaccinated with the other BoHV-4-HER-2 constructs.